All in [large type] : an autobiography - King, Billie Jean; Howard, Johnette; Vollers, Maryanne (Random House Large Print, 2021)
"In this spirited account, Billie Jean King details her life's journey to find her true self. She recounts her groundbreaking tennis career--six years as the top-ranked woman in the world, twenty Wimbledon championships, thirty-nine grand-slam titles, and her watershed defeat of Bobby Riggs in the famous "Battle of the Sexes." She poignantly recalls the cultural backdrop of those years and the profound impact on her worldview from the women's movement, the assassinations and anti-war protests of the 1960s, the civil rights movement, and, eventually, the LGBTQ+ rights movement"--